Feasibility Assessment of Cikole Hamlet Through IRTD Assessment Method as Tourism Village In Neglasari Village, Cisompet District, Garut Regency - Eka Paramita Marsongko; Yanthi Adriani; Mega Aldora; Lilis Jayanti (Politeknik Negeri Bandung, 2022)
Integrated Tourism Village Development (IRTD) proposes an intervention strategy for developing Tourism Villages in Cikole Hamlet, Neglasari Village, Garut Regency to generate opportunities for people in rural areas. This approach also aims to earn a sustainable income to complement their current earnings, contribute to equitable territorial development, and shape the environment. Neglasari Village is located in South Garut, designated as a tourism development area—encouraging the tourism industry's rural development. This village has several hamlets, one of which is the Cikole Hamlet, with the main attraction being tea, coffee, ginger, onion, and other plantations. However, the Cikole Hamlet community does not carry out the existing traditions. However, the potential of local culture can still be used as a supporting attraction and a preservation effort. For the sake of the sustainability of the existence of Neglasari Village as a tourist village, it is necessary to identify, assess and prioritize village tourism assets by using a Tourism Village Feasibility Assessment with the IRTD (Integrated Rural Tourism Development) Assessment Method to create sustainable development opportunities, in Cikole Hamlet, Neglasari Village, Garut Regency.